Diversity and Functional Dynamics of Fleshy Fruit Abscission Zones - Tranbarger, Timothy J.; Tadeo, Francisco R. (Wiley, 2020)
We examine the current knowledge about the abscission of fleshy fruit, in particular with regards to the development and function of the abscission zone (AZ). While tomato is currently the main model species to elucidate the mechanisms of fleshy fruit abscission, most studies on tomato focus on the development and function of the pedicel AZ, which is involved in both flower and ripe fruit abscission. However, the localization of the AZ within the pedicel is not the most common location of the AZ for fleshy fruit. Fleshy fruit can have one or more AZ, which can be found in different locations within the inflorescence and fruiting structure and fulfil different functions. In fact,most of the fleshy fruit species examined thus far havemore than one AZ,which can be found at the boundary between the fruit and pedicel (often referred to as the calyx AZ), within the pedicel as with tomato, at the juncture of the pedicel and peduncle or at the juncture between peduncle and shoot/branch. In addition, the different AZs may be activated or function at different stages of development, under different environmental conditions, or have a completely different purpose, such as the abscission of fruitlets or mature fruit. Together, our current knowledge about AZs suggests that while there are similarities between different AZs in different locations or from different species, not all AZs are created equal, which may be reflected in the underlying molecular mechanisms that control their development and function.